Planning of High Water Levels in Secondary Channels on the Serayu Irrigation D.I Cilacap Regency, Central Java - Melinda Ari Rohmawati; Mochammad Radja Nurdzaki; Mohammad Fauzani Nur Hafifi; Rais Amin (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Cilacap Regency in Central Java Province is recognized as an important contributor to national food production due to its extensive agricultural land and reliance on technical irrigation systems. The performance of irrigation networks, particularly secondary channels in the Serayu Irrigation Area (DI), is essential in regulating water levels to support agricultural activities in Sampang and Karangasem Villages. Variations in rainfall and field conditions often create water level differences that disrupt irrigation distribution, reducing water flow efficiency to rice fields and lowering productivity, especially during the dry season. This study aims to design secondary irrigation channels capable of maintaining stable water levels based on irrigation requirements. The research applies a descriptive quantitative method using rainfall data from BMKG, along with land area and elevation data interpreted from Google Earth imagery in 2025. The data were analyzed using probability and Thiessen polygon methods to estimate design rainfall, determine water availability, calculate irrigation demand, and plan channel dimensions. The analysis shows that Secondary Channel BGS 4.B serves an irrigation area of 103.57 hectares with a planned discharge capacity of 0.0343 m³/s. The channel design includes a base width of 0.65 meters and a water depth of 0.65 meters, with water surface elevations of 14.27 meters upstream and 13.15 meters downstream. Evaluation using a 10-year rainfall return period of 151.677 mm shows the channel can convey discharge effectively while maintaining water levels below the embankment, ensuring reliable irrigation distribution.